2017
DOI: 10.12688/f1000research.9277.3
|View full text |Cite
|
Sign up to set email alerts
|

A multi-scale computational model of the effects of TMS on motor cortex

Abstract: The detailed biophysical mechanisms through which transcranial magnetic stimulation (TMS) activates cortical circuits are still not fully understood. Here we present a multi-scale computational model to describe and explain the activation of different pyramidal cell types in motor cortex due to TMS. Our model determines precise electric fields based on an individual head model derived from magnetic resonance imaging and calculates how these electric fields activate morphologically detailed models of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 69 publications
3
17
0
Order By: Relevance
“…For our artificial model, APs are always initiated at the axon initial segment during uniform EF stimulation, and then somatic APs are elicited since this site is closest to initial segment. Such prediction is comparable to earlier modeling studies of L3/5 pyramidal neurons 49 . Further, it has been shown that the EF threshold for activating cells is tightly related to field-induced physiological responses 49 , 51 , including motor evoked potential, direct wave (D-wave) and indirect wave (I-wave).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For our artificial model, APs are always initiated at the axon initial segment during uniform EF stimulation, and then somatic APs are elicited since this site is closest to initial segment. Such prediction is comparable to earlier modeling studies of L3/5 pyramidal neurons 49 . Further, it has been shown that the EF threshold for activating cells is tightly related to field-induced physiological responses 49 , 51 , including motor evoked potential, direct wave (D-wave) and indirect wave (I-wave).…”
Section: Discussionsupporting
confidence: 90%
“…One central issue for interpreting neuromodulatory effects of magnetic or electric field stimulation is which element of targeted cells is most likely to be activated 33 , 49 . The inhomogeneity of conductance densities throughout the cell endows different elements with distinct threshold of activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, stimulations will occur at the position of the first myelin sheath, which is at the interface of gray matter (soma) and white matter (myelinated axon) (P14 in Figure 14 ). The original statement in the previous study is quoted here (Seo et al, 2016 ):…”
Section: Chapter 4 How Neurons Are Affected By the Magnetic Fieldmentioning
confidence: 92%
“…There are many recent computational studies that simulate electrical stimulation of multicompartment neuron models with realistic morphologies. Seo et al [3] modeled cortical pyramidal neurons with the activating function derived from an external TMS field, which was obtained based on an individual macroscopic head model. Goodwin & Butson [4] also modeled cortical neurons subject to an external TMS field.…”
Section: Introductionmentioning
confidence: 99%